The structure of modified silicate binding materials - D. M. Kukuj; V. A. Skvortsov; N. V. Andrianov (Литьë и металлургия)
It is indicated, that using of high-molecular substances as modifiers of alkali silicate enables to receive structured binders with interpenetrating networks.